2021
DOI: 10.1111/iep.12413
|View full text |Cite
|
Sign up to set email alerts
|

miR‐942‐5p prevents sepsis‐induced acute lung injury via targeting TRIM37

Abstract: MicroRNAs (miRNAs) have been demonstrated to play pivotal roles in the pathogenesis of sepsis‐induced acute lung injury (ALI). In this work, we aimed to clarify the potential role and the underlying mechanism of miR‐942‐5p in a lipopolysaccharide (LPS)‐induced A549 cell injury model. The cell injury was evaluated by CCK‐8 assay, flow cytometry and enzyme‐linked immunosorbent assay (ELISA). The expression levels of miR‐942‐5p and tripartite motif‐containing protein 37 (TRIM37) were measured by real‐time PCR and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…The same results were obtained by Lu, who evaluated the role of miR-942-5p, but through in vitro experiments, thus demonstrating the effects of reduction in inflammation and apoptosis only. Thanks to their experiments, they demonstrated that miR-942-5p exerts its effect by targeting and inhibiting TRIM37 [ 219 ].…”
Section: Resultsmentioning
confidence: 99%
“…The same results were obtained by Lu, who evaluated the role of miR-942-5p, but through in vitro experiments, thus demonstrating the effects of reduction in inflammation and apoptosis only. Thanks to their experiments, they demonstrated that miR-942-5p exerts its effect by targeting and inhibiting TRIM37 [ 219 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, most studies have focused on inflammation- and apoptosis-related pathways. Lu et al (12) suggested that miR-942-5p protects against LPS-induced ALI by inhibiting apoptosis and inflammation in A549 cells through negative TRIM37 regulation. Similarly, Jiang and Zhang (13) illustrated that the overexpression of lnc ZFAS1 can inhibit apoptosis and ameliorate the inflammatory responses of ALI in sepsis, possibly by targeting the expression of miR-193a-3p.…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs are non‐coding endogenous RNAs that are implicated in the diagnosis of sepsis via the control of various genes at the post‐transcriptional level through translational repression or mRNA degradation 7 . Some articles have mentioned that miRNAs could be considered to be a novel biomarker in sepsis 8,9 . Moreover, there are also studies highlighting that miRNAs could induce or suppress ALI during sepsis 10,11 .…”
Section: Introductionmentioning
confidence: 99%